PENINGKATAN HASIL BELAJAR DENGAN MODEL PROBLEM BASED LEARNING (PBL) YANG DITERAPKAN DI KELAS VIII A SISWA SMPS BUDDHIS JAYANTI - Rajagukguk, Ade Irma Suryani; Harahap, Risma Delima; Simanjuntak, Charlye (JURNAL MAHASISWA PENDIDIKAN, 2024)
This study aims to see students learning outcomes in class VIII A SMPS Buddhis Jayanti Academic Year 2023/2024 on the Human Digestive System material by applying the model of Problem Based Learning(PBL). Classroom action research (CAR) was conducted in two cycles, each cycle consisting of four stages: 1) planning, 2) implementation, 3) observation, 4) reflection, involving 24 students. Data collection is done through observation sheets, interviews, documentary coverage and tests. The results of this study indicate that the students learning outcomes in Cycle I 63%  completeness and increased to 92% completeness in cycle II. This indicates that the percentage of students learning outcomes have fulfilled standard classical, 75% of KKM 70.  The conclusion show that the learning process with the application of Problem Based Learnig (PBL) model can improve the learning outcomes of students class VIII A SMPS Buddhis Jayanti